HUBUNGAN SIKAP BELAJAR DAN MOTIVASI BELAJAR TERHADAP PRESTASI BELAJAR MATEMATIKA SISWA SMPN 6 LANGKE REMBONG - Jemudin, Frederik DE; Makur, Alberta P; Ali, Ferdinandus A (Journal of Honai Math, 2019)
The purpose of this study was to determine the relationship between learning attitudes and student learning achievement; the relationship between learning motivation and student learning achievement; and the relationship between learningattitudes and motivational learning together towards student learning achievement. The correlational research method carried out this research. The population in this study were seventh-grade students of Langke Rembong 6 Junior High School, East Nusa Tenggara. Samples as subjects in this study were 46 students. Data collection was conducted using a questionnaire to obtain data on learning attitudes and learning motivation while the test instrument was used to gather data on mathematics learning achievement. The results showed that there was a positive and significant relationship between learning attitudes towards students' mathematics learning achievement. There is also a positive and significant relationship between learning motivation towards students' mathematics learning achievement. Furthermore, there is a positive and significant relationship between learning attitudes and learning motivation towards students' mathematics learning achievement together.